The motives of exposure of the Saudi elites to citizen journalism and their relation to the news reporting role - Al-Juaaid, Manal Mueed (Arab Journal for Sciences and Research Publishing, 2018)
The study aimed to identify the motives of the exposure of the Saudi media elite to citizen journalism and their relationship to the news role And monitor and characterize the mechanisms upon which the Saudi media elite depends on the application of professional standards in line with the nature of the news role produced by the citizen. A sample of the study(205) was selected from media elite of different types (press, radio, television, electronic sites for newspapers). The study found that citizen journalism sites are always followed by respondents. The largest percentage of respondents rely on electronic news sites as sources of access to news on the media. World wide web. The social media networks ("Facebook, My space") topped the most popular forms in the citizen’s press. The news articles received the largest percentage of follow-up of the respondents, and then the video clips and pictures, which confirms the role played by citizen journalism as an intermediary for the media. The results of the study also showed the diversity and multiple motives for exposure to citizen journalism on the Internet. This can be attributed to the failure of the traditional media to meet the needs of news and information, the persistence of certain policies, the great technological development and the virtual space that has helped the growth of this type of media.